2021
DOI: 10.1093/ndt/gfab024
|View full text |Cite
|
Sign up to set email alerts
|

Does kidney transplantation with a standard or expanded criteria donor improve patient survival? Results from a Belgian cohort

Abstract: Background Changes in recipient and donor factors have reopened the question of survival benefits with kidney transplantation versus dialysis. Methods We analyzed survival among 3808 adult Belgian patients waitlisted for a first deceased donor kidney transplant from 2000 to 2012. The primary outcome was mortality during the median waiting time plus 3 years of follow-up after transplantation or with continued dialysis. Outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 24 publications
2
24
0
3
Order By: Relevance
“…We identified 48 studies eligible for this systematic review. 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 After data extraction and further screening, we found 18 studies containing sufficient non-overlapping outcome data suitable for meta-analysis. 24 27 30 31 32 33 34 36 42 48 50 52 61 62 64 66 67 68 Figure 1 shows a PRISMA flow diagram detailing the process of study selection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 48 studies eligible for this systematic review. 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 After data extraction and further screening, we found 18 studies containing sufficient non-overlapping outcome data suitable for meta-analysis. 24 27 30 31 32 33 34 36 42 48 50 52 61 62 64 66 67 68 Figure 1 shows a PRISMA flow diagram detailing the process of study selection.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen of the 44 studies reported adjusted relative hazards stratified by donor type. In all cases, where respective comparisons were available, studies reported living donor transplantation as conferring a greater survival benefit over deceased donor transplantation, 31 35 45 49 55 59 60 61 63 standard criteria donors over extended criteria donors, 41 47 55 60 69 and finally hepatitis C virus seronegative over hepatitis C virus seropositive donor transplantation. 37 65 Detailed outcome data with adjusted hazard ratios for each study and stratum are provided in supplementary table D. Benefit was found in all adults aged ≥18, older adults (≥60, 24 28 29 38 47 66 67 ≥65, 28 55 58 61 and ≥70 45 50 62 ), and population groups with obesity (body mass index ≥30), 35 diabetes as a comorbidity, 43 44 58 systemic sclerosis, 39 peripheral arterial disease, 43 60 and patients seropositive for hepatitis C virus.…”
Section: Resultsmentioning
confidence: 99%
“…14,15 Only a minority of older dialysis patients have neither cardiovascular comorbidity nor diabetes, raising the question whether KT in general should be offered to elderly with ESKD. 8,15,16 Optimizing outcomes in older KT recipients requires allocation of all available organs in carefully selected candidates, whose transplantation risk is lower than their expected benefit; however, a lack of consensus regarding which recipient factors should be considered during the evaluation process 17 has resulted in various selection policies between transplant centers. In the current study, we aimed to describe posttransplant patient survival in older patients who were transplanted with kidneys from deceased brain-dead (DBD) donors and to identify which pretransplant recipient factors were associated with patient survival after KT and if they could potentially guide therapeutic decisions.…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 15 Only a minority of older dialysis patients have neither cardiovascular comorbidity nor diabetes, raising the question whether KT in general should be offered to elderly with ESKD. 8 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…ECD kidney allograft survival may be improved in the absence of circulating donor-specific antibody ( p < 0.001) and CIT <12 h ( p = 0.030) according to a French study ( 22 ). Optimal utilization of ECD kidneys may also be stratified by recipient age, with studies suggesting recipients aged ≥60 years ( 23 ) or ≥65 years ( 24 ) be prioritized. However, while a 1.75-fold (95% CI 1.53–2.00, p < 0.0001) increased risk for graft failure using ECD versus SCD kidneys was observed in one study, population-average effect using propensity scores with 10-year follow-up highlighted a minimal absolute effect of only 8 months (95% CI 2–14 months) quicker time to graft failure attributed to ECD kidneys ( 24 ).…”
Section: Donor Clinical Factorsmentioning
confidence: 99%